“ҲУҚУҚИЙ КОМПЕТЕНТЛИК” ТУШУНЧАСИНИНГ НАЗАРИЙ ТАВСИФИ - Тлеуов, Е. (SCIENCE and SOCIETY, 2018)
It is stated in the article that forming an individual, particularly, legal competence in students is one of the actual problems. The article exposes the essence and theoretical characteristics of the notion ―legal competence‖ based on the study of research works devoted to the mentioned problem and analysis of suggested ideas. The author defines the notion ―legal competence‖ taking into account the theoretical approaches of the group of researchers.
Keywords: ҳуқуқ; компетентлик; касбий компетентлик; ҳуқуқий компетентлик; “ҳуқуқий компетентлик” тушунчасининг назарий тавсифи